Nurses’ knowledge and practice regarding intravenous therapy in a teaching hospital, Bharatpur - Lamsal, Sandhya; Shrestha, Rosy (Journal of Chitwan Medical College, 2019)
Background: Intravenous (IV) therapy is a common procedure in clinical setting of any hospital and nurses are accountable for handling and management to the patient with IV therapy. However, various serious medical complications were arisen due to nurses having inadequate knowledge and practice on IV therapy. Therefore, this study was conducted to find out the nurses’ knowledge and practice regarding IV therapy in a teaching hospital, Bharatpur, Chitwan. Methods: A cross- sectional study design was adopted with 177 nurses for assessment to knowledge and 53 nurses to observe practice on IV therapy. A systematic random sampling technique was used. Data were collected by using semi-structured, self-administered questionnaire for identifying knowledge and observation checklist for observing the practice of IV therapy among nurses. The data was analyzed using descriptive and inferential statistic. Results: The level of knowledge was found inadequate and level of practice was found unsatisfactory on IV therapy. The associated factors with level of knowledge regarding IV therapy were age (p=0.012), professional qualification (p=0.001), professional designation (p=0.005), professional experience (p=0.002) and in-service education (p=0.003). Similarly, the associated factors with level of practice on IV therapy were professional qualification (p=0.020) and professional designation (p=0.04). Conclusions: It is concluded that most of the nurses had inadequate knowledge and unsatisfactory practice on IV therapy. Hence, it is strongly recommended for need of protocol for IV therapy, in-service education, effective supervision and reinforcement for improvement of knowledge and practice regarding IV therapy among nurses.